2020
DOI: 10.15252/embj.2019103957
|View full text |Cite
|
Sign up to set email alerts
|

Microtubules control nuclear shape and gene expression during early stages of hematopoietic differentiation

Abstract: Hematopoietic stem and progenitor cells (HSPC) can differentiate into all hematopoietic lineages to support hematopoiesis. Cells from the myeloid and lymphoid lineages fulfill distinct functions with specific shapes and intra-cellular architectures. The role of cytokines in the regulation of HSPC differentiation has been intensively studied but our understanding of the potential contribution of inner cell architecture is relatively poor. Here, we show that large invaginations are generated by microtubule const… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 70 publications
2
40
1
Order By: Relevance
“…EV1B,C). Resting B cells, displayed a lobular shaped nucleus (between 3 or 4 lobes), where the MTOC was closely associated inside the main nuclear groove or within a principal intra-lobular space, similar to recently described studies in hematopoietic cells (Biedzinski et al, 2020)(Fig. EV1A-B).…”
Section: B Cells Change Their Nuclear Morphology and Re-orientate Their Nuclear Groove Toward The Immune Synapsesupporting
confidence: 86%
“…EV1B,C). Resting B cells, displayed a lobular shaped nucleus (between 3 or 4 lobes), where the MTOC was closely associated inside the main nuclear groove or within a principal intra-lobular space, similar to recently described studies in hematopoietic cells (Biedzinski et al, 2020)(Fig. EV1A-B).…”
Section: B Cells Change Their Nuclear Morphology and Re-orientate Their Nuclear Groove Toward The Immune Synapsesupporting
confidence: 86%
“…For example, recent findings demonstrate that dynein motors drive and coordinate spatial alignment of radially organized MT networks, centering MTOCs at the geometrical or mechanical center of the actomyosin network of the cell 33,34 . Dyneins also control cell-type-specific changes in the cell architecture that drive downstream functional adaptations; i.e., in neurons, dyneins drive MT sliding and extension along the axonal axis [35][36][37][38] , while in hematopoietic cell lineages, dyneins generate tensile forces in MT networks that surround the cell nucleus and ultimately result in the formation of nucleus-compressing 3D MT meshworks that favor mechanosensory activation of chromatin towards myeloid (and away from lymphoid) differentiation 39 . Meanwhile, kinesins demonstrate similar mechanical and MT-restructuring effects, but in apparent opposition to the actions of dyneins.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent studies suggest the stability of heterochromatin at the nuclear periphery also has an important gene regulatory function supporting gene transcription in euchromatic regions [ 31 ], and that this peripheral localisation of heterochromatin may also guide the three-dimensional positioning of chromosomes into multi-lobed neutrophil nuclei [ 32 ]. Interestingly, a recent study has shown that the nuclei of HSCs undergo dramatic morphological changes during myeloid or lymphoid differentiation [ 33 ]. Surprisingly, these morphological changes do not seem to be a consequence of a softening of the nuclear lamina, but rather are driven by cytoplasmic microtubules squeezing the nucleus to form large deformations altering chromatin organisation, causing localised loss of H3K9me3 and H3K27me3, and altering gene expression [ 33 ].…”
Section: Classical Heterochromatin In Haematopoiesismentioning
confidence: 99%
“…Interestingly, a recent study has shown that the nuclei of HSCs undergo dramatic morphological changes during myeloid or lymphoid differentiation [ 33 ]. Surprisingly, these morphological changes do not seem to be a consequence of a softening of the nuclear lamina, but rather are driven by cytoplasmic microtubules squeezing the nucleus to form large deformations altering chromatin organisation, causing localised loss of H3K9me3 and H3K27me3, and altering gene expression [ 33 ]. This new frontier of the mechanobiology will likely reveal further important roles of heterochromatin in haematopoiesis.…”
Section: Classical Heterochromatin In Haematopoiesismentioning
confidence: 99%